Après le tremblement de terre au Japon : la mission transnationale de la sociologie - Kazuhisa Nishihara (Socio, 2015)
East Asia has recently seen increased mobility among various groups of people, including foreign workers, intermarried migrants, international students, and tourists. However, political relations among Northeast Asian countries (especially, the People’s Republic of China, Republic of Korea, and Japan) have been strained due to actually territorial disputes and other conflicts. As a Japanese theoretical sociologist living in Japanese society, I want to examine the transnational communications or exchanges among these nations and to explore future directions for achieving mutual understanding among the people of Northeast Asia. However, in this paper, the political and economic conflicts themselves will not be my main theme. Instead, I will focus on the problem of socio-cultural communications and exchanges around the great earth quake and tsunami of 2011.This paper has the following 3 aims: (1) to grasp contemporary Japanese society from a viewpoint of transnational communications, especially socio-cultural exchanges among Northeast Asian people, (2) to present a methodological standpoint to sketch the future image of mutual understanding among Asian/Transpacific/global areas on the basis of my field research, and (3) to re-examine Japanese sociology and its relationship with the Western sociological tradition through these investigations.